Consensus-Expressed CXCL8 and MMP9 Identified by Meta-Analyzed Perineural Invasion Gene Signature in Gastric Cancer Microarray Data - Jia, Xiuzhi; Lu, Minjia; Rui, Chen; Xiao, Ying (Frontiers in Genetics, 2019)
As an underrecognized route of cancer metastasis, perineural invasion (PNI) is defined as the neoplastic invasion of nerves, which can be targeted to inhibit the metastasis of malignant cancer. However, the mechanism underlying PNI in cancer is largely unknown. We constructed a PNI gene signature based on a Pathway Studio–mediated literature screen and investigated the relevant genes in a gastric cancer model. Thus, a total of 467 studies/datasets were retrieved from the Gene Expression Omnibus database using the keyword “gastric cancer,” among which 13 studies that focused on gene expression profiling were further manually inspected and selected. Furthermore, the constructed PNI gene signature (104 genes) expression was meta-analyzed, and the consensus-expressed C-X-C motif chemokine ligand 8 (CXCL8) and matrix metallopeptidase 9 (MMP9) (p < 0.01, |log fold change| >1) were detected. Importantly, the disease-free survival was significantly worse in patients with high expressions of CXCL8 and MMP9 than in those with low expressions (p = 0.05). Moreover, multiple linear regression analysis showed that the population region (country) was associated with the expressions of both CXCL8 and MMP9. In conclusion, these data suggest that the coexpression of CXCL8 and MMP9 could be an early detection marker for PNI, with a potential to be utilized as individual therapy targets for early treatment to prevent PNI-related cancer metastasis.